Accessing electron-deficient π-extended pyrenes via non-K-region fusion - Dongre, Sangram D.; Kumar, Viksit; Kumar, Ravi; Babu, Sukumaran Santhosh (ORGANIC LETTERS, 2025)
This study presents a new class of pyrene derivatives featuring non-K-region fusion and electron-deficient pi-extension. By strategically introducing electron-withdrawing groups at the non-K positions, the optical and redox properties of these compounds were significantly altered. For the first time, we report a non-K-region fused acceptor pyrene with an extended pi-skeleton. The detailed characterizations revealed pronounced shifts in both absorption and emission spectra, accompanied by a significant lowering of the LUMO energy levels. Our results highlight non-K region-fused pyrenes as a promising building block for next-generation organic semiconductors with tunable electronic properties.